Transition to Higher Education: lifestyle changes, health condition and academic success of first-year students - Soares, Andreia (2013)
Lifetime normative transitions comprising significant ecological structural changes, as the transition to higher education, represent a risk factor in the adoption and maintenance of less healthy lifestyles. Health-related behaviors and attitudes (HBA) that form part of personal lifestyle are variables that affect students’ health condition and academic success. A sample of first-year students (N = 546) from the University of Coimbra (academic year: 2009/2010) was collected in order to study “students in transition” lifestyle (viz. HBA changes; perceived impact on health condition, adaptation process and academic performance; intended changes), health condition, quality of the adaptation process and academic performance, as well as the associations among these variables. Although the prevalence of HBA had changed after university entry, most of the students maintained a high number of positive HBA but exhibited alarming levels of alcohol consumption and physical activity. The two previously mentioned HBA seemed to play an important yet conflicting role in health condition and academic success. Most of the results are consistent with the literature and provided important information for planning an initiative focused on promoting health and academic success in this specific context.